Trial Evaluation of Protection and Immunogenicity of Piscine Bivalent Streptococcal Vaccine: From the Lab to the Farms - Korntip Kannika; Soranut Sirisuay; Hidehiro Kondo; Ikuo Hirono; Nontawith Areechon; Sasimanas Unajak (Vaccines, 2022)
Streptococcosis is one of the major diseases that causes devastation to farmed fish, leading to significant economic losses all around the world. Currently, two serotypes of Streptococcus agalactiae, serotype Ia and III, have been identified as virulent strains and major causative agents of the disease in farmed Nile tilapia (Oreochromis niloticus Linn.) in Thailand. Upon inactivated vaccine development, monovalent inactivated whole-cell vaccines demonstrated high specific antibody production against homologous serotypes and limited production with heterologous serotypes. However, for higher efficacy, a bivalent streptococcal vaccine was designed to maximize protective immunity to both serotypes. Interestingly, our bivalent vaccine could successfully induce specific antibody production against both serotypes with similar levels, and the response could extend over the 8 weeks of the experimental period. Evaluation of vaccines in the laboratory scale revealed relative percent survival (RPS) of vaccinated tilapia to serotype Ia (81.2 ± 9.4%) and serotype III (72.2 ± 4.8%), respectively. The efficacy of the bivalent vaccine showed significant RPS higher than the monovalent vaccine (p < 0.05) at 30 days, and the protection of all those vaccines was reduced thereafter. Evaluation of the vaccine in a farm trial in different locations in Thailand revealed the efficacy of the bivalent vaccine in increasing the production yield by greater than 80% in all tested farms in 2015 and 2021. Taken together, this study affirms the efficacy of the bivalent streptococcal vaccine in the prevention of streptococcus disease in Nile tilapia, which could be used in different areas. This vaccine development could be effectively applied in the tilapia culture industry.